LABOR, MATERIAL REPRODUCTION AND PRICE FORMATION IN CAPITALIST DEVELOPMENT (Desenvolvimento em Questão, 2020)
In this text is developed an approach of the relations between the price formation process and capitalist development whose starting point is the working process in its articulation with the material reproduction of society. Methodologically, this is expressed by considering the monetary aggregation of value based on working time as the basic process of price formation, according to Marx's theory of value. From the demonstration that the added value is the economic category that permits analyzing the articulation of the working process with the material reproduction of society, in this article it was also demonstrated that such reproduction can be characterized as a process in which wealth, values ​​and prices, although subject to class struggle, they determine each other over time. In this process, it was evidenced that a stable equalization of profit rates can hardly occur. On the contrary, the adoption of the profit rate as a microeconomic criterion of decision on which its continuous equalization is based, as well as the differentiation of the aggregated value of the monetary equivalent of the working time caused by the global process of equalization of the profit rates, they result in an allocative inefficiency that is inherent to the capitalism. Thus, capitalist production, because it’s determined by the dynamics of capital accumulation itself, contradicts social needs. Due to its disturbing effects on the material reproduction of society, such a contradiction can be considered as one of the fundamental causes of the unequal character of capitalist development.
Keywords: Marx's theory of value. Social reproduction. Unequal development.